Práticas alimentares de gestantes e mulheres não grávidas: Há diferenças? - Gomes, Caroline De Barros [UNESP]; Malta, Maíra Barreto [UNESP]; De Almeida Martiniano, Ana Carolina [UNESP]; Di Bonifácio, Luiza Pereira [UNESP]; De Barros Leite Carvalhaes, Maria Antonieta [UNESP] (My University, 2015)
PURPOSE: To determine the eating behavior of pregnant women assisted by primary health care and to compare it with women at childbearing age in Brazilian capitals. METHODS: A cross-sectional study conducted on 256 pregnant women in the second trimester of gestation, selected by drawing lots from those assisted by primary health care units of a municipality in the state of São Paulo in 2009/2010. Eating habits were investigated via a questionnaire adapted from the VIGITEL system, consisting of questions about eating habits in general and the frequency and consumption characteristics of food groups/specific foods. For tis comparison, we used the indicators reported by the VIGITEL system for women at childbearing age in Brazilian capitals in 2010. The analyses involved the presentation of frequency distribution and descriptive statistics with comparisons according to the age group. RESULTS: Most patients had breakfast every day (86.7%) and 45.7% habitually exchanged a main meal for a snack once or twice a week. A daily consumption of fruit, raw salad and vegetables was not reported by 48.8%, 41.8% and 55.1% of the women, respectively. Fish was reported to never or almost never be consumed by 64.4% of the pregnant women. At least once a week, 69.9% of them reported the consumption of soda, and 86.4% of wafers/cookies. The comparison between the pregnant women and women at childbearing age in capitals showed a close similar prevalence of overweight, and no difference in the regular consumption of fruit and vegetables. Meat containing excess of fat and whole milk were more consumed by pregnant women, with differences reported in all the age groups analyzed. On the other hand, the pregnant women reported a less regular intake of soft drinks. CONCLUSIONS: The actions that need to be performed in prenatal care are various and very important, promoting the consumption of specific foods and providing guidelines about eating behavior, while reinforcing healthy eating habits already present.
Eating habits of pregnant and non-pregnant women: Are there differences?
Keywords: Food habits; Pregnancy; Pregnant women; Prenatal nutrition; Women’s health